Effects of growth hormone withdrawal in obese premenopausal women. (22nd April 2013) - Lin, E.; Bredella, M. A.; Gerweck, A. V.; Landa, M.; Schoenfeld, D.; Utz, A. L.; Miller, K. K.
Abstract Objective We previously reported improved body composition and cardiovascular risk markers plus a small decrease in glucose tolerance with GH administration vs placebo for 6 months to abdominally obese premenopausal women. The objective of this study was to determine whether the effects of GH treatment on cardiovascular risk markers, body composition and glucose tolerance in obese women persist 6 months after GH withdrawal. Design and patients Fifty abdominally obese premenopausal women completed a trial of rhGH vs placebo for 6 months; thirty‐nine women completed a subsequent 6‐month withdrawal observation period. Measurements IGF‐I, body composition by CT, 1H‐MRS and DXA, serum cardiovascular risk markers, oral glucose tolerance test (OGTT). Results IGF‐I standard deviation scores (SDS) within the GH group were −1·7 ± 0·1 (pretreatment), −0·1 ± 0·3 (after 6 months of GH) and −1·7 ± 0·1 (6 months post‐GH withdrawal). Six months after GH withdrawal, total abdominal and subcutaneous adipose tissue, total fat, trunk fat, trunk/extremity fat, hsCRP, apoB, LDL, and tPA were higher than at the 6‐month (GH discontinuation) timepoint (P ≤ 0·05). All body composition and cardiovascular risk markers that had improved with GH returned to baseline levels by 6 months after GH discontinuation, as did fasting and 2‐h OGTT glucose levels. Conclusion The effects of GH administration to abdominally obese premenopausal women have a short time‐course. The beneficial effects on body composition and cardiovascular risk markers, and the side effect of altered glucose tolerance returned to pretreatment levels after GH withdrawal. There was no suppression of endogenous IGF‐I levels, which returned to baseline after GH withdrawal.